IDENTIFICAÇÃO MOLECULAR, FILOGENIA E POTENCIAL CELULOLÍTICO DE FUNGOS FILAMENTOSOS TERMOFÍLICOS ISOLADOS DE FLORESTA OMBRÓFILA MISTA - Antoneli, Marcio André (2018)
β-glucosidases have been extensively used in a variety of industrial sectors: in jeans stonewashing and textile maturation processes, wine production, pharmaceutical industry, saccharification of cellulosic biomass for biofuels production. Screening of thermophilic fungi is the way to obtain rich sources of new and powerful enzymes, better than those related to mesophilic strains, and give us relevant information about genetic diversity and ecology of these microorganisms. Furthermore, efforts to build robust and evolutionary hypotheses have been the main goal on research papers with regard to investigate and give a light on species evolution patterns. The aim of this study was to discover β-glucosidase producing thermophilic fungi from soil and litterfall of fragments from Araucaria Forest, Brazil. Passion fruit peel was utilized as substrate to evaluate enzyme production, in submerged fermentation, with Central Composite Desing (CCD) method. Biochemical characterization of βglucosidases from the best producer were done. Species identification by molecular ribosomal marker Internal Transcribed Spacers (ITS) were done, as well as the putative phylogenetic hypotheses, utilizing Maximum Parsimony, Maximum Likelihood, and Bayesian Inference. Eight lineages morphologically distinct were selected. Seven of them were identified as distinct species. Nonetheless, Thermoascus crustaceus lineage was chosen as the best βglucosidase producer, with the optimization process utiling 2.9 % of passion fruit peel, for 8.6 days, in pH 7.8 at 45 ºC, corresponding a total of 20.08 U/mL, twice of the initial value. Furthermore, β-glucosidase activity was high at 70 ºC in pH 5.0, with low stability to pH range between 6.5 to 7.5 with residual activity up to 63%. Thermal stability was at 60 ºC. Thielavia terrestris, Thermoascus crustaceus, Aspergillus fumigatus, Rhizomucor miehei, Rhizomucur pusillus and Rhizopus microsporus species ware identified. Only one lineage belonging to Thielavia genera it was not possible to discrimine at the species level using this marker. Phylogeny of these species were assembled, with particular importance regard of the thermophilic lineages of brazillian soils, until now is inexistent.